Our ncert solutions for Exercise 4.1 Class 11 maths 4. Principle Of Mathematical Induction - ncert solutions - Toppers Study is the best material for English Medium students cbse board and other state boards students.

# Exercise 4.1 Class 11 maths 4. Principle Of Mathematical Induction - ncert solutions - Toppers Study

Topper Study classes prepares ncert solutions on practical base problems and comes out with the best result that helps the students and teachers as well as tutors and so many ecademic coaching classes that they need in practical life. Our ncert solutions for Exercise 4.1 Class 11 maths 4. Principle Of Mathematical Induction - ncert solutions - Toppers Study is the best material for English Medium students cbse board and other state boards students.

## Exercise 4.1 Class 11 maths 4. Principle Of Mathematical Induction - ncert solutions - Toppers Study

CBSE board students who preparing for **class 11 ncert solutions maths and Mathematics** solved exercise **chapter 4. Principle Of Mathematical Induction** available and this helps in upcoming exams
2024-2025.

### You can Find Mathematics solution Class 11 Chapter 4. Principle Of Mathematical Induction

- All Chapter review quick revision notes for chapter 4. Principle Of Mathematical Induction Class 11
- NCERT Solutions And Textual questions Answers Class 11 Mathematics
- Extra NCERT Book questions Answers Class 11 Mathematics
- Importatnt key points with additional Assignment and questions bank solved.

NCERT Solutions do not only help you to cover your syllabus but also will give to textual support in exams 2024-2025 to complete **exercise 4.1 maths class 11 chapter 4** in english medium. So revise and practice these all cbse study materials like class 11 maths chapter 4.1 in english ncert book. Also ensure to repractice all syllabus within time or before board exams for ncert class 11 maths ex 4.1 in english.

See all solutions for class 11 maths chapter 4 exercise 4 in english medium solved questions with answers.

### Exercise 4.1 class 11 Mathematics Chapter 4. Principle Of Mathematical Induction

Sure! The following topics will be covered in this article

- Exercise 4.1 Class 11 Maths 4. Principle Of Mathematical Induction - Ncert Solutions - Toppers Study
- Class 11 Ncert Solutions
- Solution Chapter 4. Principle Of Mathematical Induction Class 11
- Solutions Class 11
- Chapter 4. Principle Of Mathematical Induction Exercise 4.1 Class 11

**Notice**: Undefined offset: 5 in

**/home/atpeduca/public_html/toppersstudy.com/view-home.php**on line

**123**

## 4. Principle Of Mathematical Induction

### | Exercise 4.1 |

## Exercise 4.1 Class 11 maths 4. Principle Of Mathematical Induction - ncert solutions - Toppers Study

**Chapter 4. Principle of Mathematical induction **

**Exercise 4.1 **

Prove the following by using the principle of mathematical induction for all *n *∈ **N**:

**Solution: **

Let the given statement be P(*n*), i.e.,

LHS = RHS

Thus P(*k *+ 1) is true, whenever P (*k*) is true.

Hence, from the principle of mathematical induction, the statement P(*n*) is true for all natural numbers n.

**Solution: **

Let the given statement be P(*n*), i.e.,

LHS = RHS

Thus P(*k *+ 1) is true, whenever P (*k*) is true.

Hence, from the principle of mathematical induction, the statement P(*n*) is true for all natural numbers n.

**Solution:** Let the given statement be P(n), so

Thus P(*k *+ 1) is true, whenever P (*k*) is true.

Hence, from the principle of mathematical induction, the statement P(*n*) is true for all natural numbers n.

**Q19. ***n ***( n + 1) (n + 5) is a multiple of 3.**

**Solution: **

Let the given statement be P(n), so

P(n) : *n *(*n *+ 1) (*n *+ 5) is a multiple of 3.

For n = 1, so we have;

*n *(*n *+ 1) (*n *+ 5) = 1 × 2 × 6 = 12 = 3 × 4

P(n) is true for n = 1

Assume that P(k) is also true for some positive integer k.

k(k + 1) (k + 5)

= k^{3} + 6k^{2} + 5 k = 3m (say) ……………….. (1)

Now, we shall prove that P(k + 1) is true whenever P(k) is true

Replacing k by k + 1

k + 1 (k + 2) (k + 6)

= (k + 1) (k^{2} + 8k + 12)

= k (k^{2} + 8k + 12) + 1(k^{2} + 8k + 12)

= k^{3} + 8k^{2} + 12k + k^{2} + 8k + 12

= k^{3} + 9k^{2} + 20k + 12

=( k^{3} + 6k^{2} + 5 k) + 3k^{2} + 15k + 12

= 3m + 3k^{2} + 15k + 12 from (1)

= 3(m + k^{2} + 5k + 4)

∴ k + 1 (k + 2) (k + 6) is multiple of 3

Thus P(*k *+ 1) is true, whenever P (*k*) is true.

Hence, from the principle of mathematical induction, the statement P(*n*) is true for all natural numbers n ∈ N.

**Q20. 10 ^{2n - 1 } + 1 is divisible by 11. **

**Solution: **

Let the given statement be P(n), so

P(n) : 10^{2n - 1 } + 1 is divisible by 11.

For n = 1, so we have;

10^{2n - 1 } + 1 = 10^{2}^{×}^{1 - 1} + 1 = 10 + 1 = 11

P(n) is true for n = 1

Assume that P(k) is also true for some positive integer k.

10^{2k- 1 } + 1 = 11m say

10^{2k- 1 } = 11m - 1 ……………… (1)

We shall prove that P(k + 1) is true whenever P(k) is true

∴ replacing k by k + 1 we have

10^{2k - 1 } + 1

= 10^{2k + 1 } + 1

= 10^{2k} × 10^{1} + 1

= {10^{2k - 1} × 100 + 1}

= {(11m - 1)× 100 + 1} from equation (1)

= 1100m - 100+ 1

= 1100m - 99

= 11(100m - 9)

∴ 10^{2n - 1 } + 1 is divisible by 11

Thus P(*k *+ 1) is true, whenever P(*k*) is true.

Hence, from the principle of mathematical induction, the statement P(*n*) is true for all natural numbers n ∈ N.

**Q21. ***x*^{2n}**– y^{2n} is divisible by x + y**

**Solution:** Let the given statement be P(n), so

P(n) : x^{2n} – y^{2n} is divisible by x + y

Putting n = 1 we have,

x^{2n} – y^{2n} = x^{2} - y^{2} = (x + y) (x - y)

P(n) is true for n = 1

Assume that P(k) is also true for some positive integer k or

x^{2k} – y^{2k} is divisible by (x + y)

So, x^{2k} – y^{2k} = m( x + y)

Or x^{2k} = m( x + y) + y^{2k} …………. (1)

We shall prove that P(k + 1) is true whenever P(k) is true

∴ replacing k by k + 1 we have

x^{2k + 2} – y^{2k + 2}

= x^{2k }. x^{2} – y^{2k }.y^{2}

Putting the value of x^{2k} from (1)

= {m( x + y) + y^{2k}} x^{2} – y^{2k }.y^{2}

= m( x + y) x^{2} + y^{2k}. x^{2} – y^{2k }.y^{2}

= m( x + y) x^{2} + y^{2k} (x^{2} – y^{2})

= m( x + y) x^{2} + y^{2k} (x + y) ( x - y)

= ( x + y) [mx^{2} + y^{2k} ( x - y)]

∴ x^{2n} – y^{2n} is divisible by x + y

Thus P(*k *+ 1) is true, whenever P(*k*) is true.

Hence, from the principle of mathematical induction, the statement P(*n*) is true for all natural numbers n ∈ N.

**Q22. ****3 ^{2n+2} – 8n – 9 is divisible by 8**

**Solution:** Let the given statement be P(n), so

P(n) : 3^{2n+2} – 8*n *– 9 is divisible by 8

Putting n =1

P(1) : 3^{2×1+2} – 8 *× 1 *– 9 = 81 - 17 = 64 = 8 × 8

Which is divisible by 8

∴ P(1) is true

Assume that P(k) is also true for some positive integer k

3^{2k + 2} – 8*k *– 9

3^{2k + 2} – 8*k *– 9 is divisible by 8

3^{2k + 2} – 8*k *– 9 = 8m

Or 3^{2k + 2} = 8m + 8*k *+ 9 ……………. (1)

We shall prove that P(k + 1) is true whenever P(k) is true

∴ replacing k by k + 1 we have

3^{2k + 4} – 8*k *–* 8 *– 9

= 3^{2k + 4} – 8*k *–* 17*

= 3^{2k + 2} × 3^{2} – 8*k *–* 17*

= (8m + 8*k *+ 9)× 9 – 8*k *–* 17*

= 72m + 72*k *+ 81 – 8*k *–* 17*

= 72m + 64*k *+ 64

= 8(9m + 8*k *+ 8)

∴ 3^{2n+2} – 8*n *– 9 is divisible by 8

Thus P(*k *+ 1) is true, whenever P(*k*) is true.

*n*) is true for all natural numbers n ∈ N.

**Q23. ****41^{n} – 14^{n} is a multiple of 27.**

**Solution:** Let the given statement be P(n), so

P(n) : 41* ^{n} *– 14

*is a multiple of 27*

^{n}Putting n = 1

P(1): 41* ^{n} *– 14

*41 – 14 = 27*

^{n}=∴ P(1) is true

Assume that P(k) is also true for some positive integer k

41* ^{k} *– 14

*= 27*

^{k}41* ^{k} *= 27 + 14

*(1)*

^{k}…………We shall prove that P(k + 1) is true whenever P(k) is true

∴ replacing k by k + 1 we have

41* ^{k + 1} *– 14

^{k + 1 }= 41* ^{k }. *41 – 14

*. 14*

^{k }= (27 + 14* ^{k}*) 41 – 14

*. 14*

^{k }= 27 . 41 + 14* ^{k} .*41 – 14

*. 14*

^{k }= 27 . 41 + 14* ^{k} *(41 – 14 )

= 27 . 41 + 14* ^{k} *. 27

= 27 ( 41 + 14* ^{k} *)

∴ 41* ^{n} *– 14

*is a multiple of 27*

^{n}Thus P(

*k*+ 1) is true, whenever P(

*k*) is true.

*n*) is true for all natural numbers n ∈ N.

**Q24. (2n + 7) < (n + 3) ^{2}**

**Solution:** Let the statement be p(n) so,

p(n) : (2n + 7) < (n + 3)^{2}

=> p(1) : (2 × 1 + 7) < (1 + 3)^{2}

=> 9 < 4^{2}

=> 9 < 16

Therefore, p(1) is true so Assume that p(k) is also true for some integer k.

(2k + 7) < (k + 3)^{2} ......... (i)

Now we shall prove for p(k + 1)

2(k +1) + 7 < (k + 1 + 3)^{2}

2k + 2 + 7 < (k + 4)^{2} ........ (ii)

We have from (i)

(2k + 7) < (k + 3)^{2}

Adding 2 both sides

=> 2k + 7 + 2 < (k + 3)^{2} + 2

=> 2k + 7 + 2 < k^{2} + 6k + 9 + 2

=> 2k + 7 + 2 < k^{2} + 6k + 9 + 2

=> 2k + 7 + 2 < k^{2} + 6k + 11

Now, k^{2} + 6k + 11 < (k + 4)^{2} from (ii)

=> 2k + 7 + 2 < k^{2 }+ 6k + 11 < k^{2} + 8k + 16

=> 2k + 2 + 7 < k^{2} + 8k + 16

=> 2(k + 1) + 7 < (k + 4)^{2}

=> 2(k + 1) + 7 < (k + 1 + 3)^{2}

Thus P(*k *+ 1) is true, whenever P(*k*) is true.

*n*) is true for all natural numbers n ∈ N.

##### Other Pages of this Chapter: 4. Principle Of Mathematical Induction

### Select Your CBSE Classes

Important Study materials for classes 06, 07, 08,09,10, 11 and 12. Like CBSE Notes, Notes for Science, Notes for maths, Notes for Social Science, Notes for Accountancy, Notes for Economics, Notes for political Science, Noes for History, Notes For Bussiness Study, Physical Educations, Sample Papers, Test Papers, Mock Test Papers, Support Materials and Books.

*Mathematics Class - 11th*

NCERT Maths book for CBSE Students.

books

## Study Materials List:

##### Solutions ⇒ Class 11th ⇒ Mathematics

## Topper's Study

New Books